Use of Low Molecular Weight Heparin in Pregnancy - Melissari, Euthemia; Parker, Christopher J; Wilson, Noel V; Monte, Giovanni; Kanthou, Chryso; Pemberton, Kieran D; Nicolaides, Kypros H; Barrett, John J; Kakkar, Vijay V (Thrombosis and Haemostasis, 1992)
In a controlled study of 15 pregnant patients undergoing therapeutic termination of pregnancy, seven received subcutaneously 5,000 anti-FXa units of low molecular weight (LMW) heparin 15 and 3 h prior to the termination, and eight patients acted as controls. Paired maternal and fetal blood samples were taken (before or immediately after the termination) for assay of heparin activity by a chromogenic anti-FXa method sensitive to levels of 0.02 anti-FXa U/ml. LMW heparin was detected in all maternal samples of the test patients but was not detected in any of the fetal samples.The use of LMW heparin as a thromboprophylactic agent was then evaluated in 11 patients who were known to have a severe thromboembolic tendency, had suffered recurrent miscarriages and had responded poorly to conventional anticoagulation (oral anticoagulant, conventional heparin). All patients receiving LMW heparin in thromboprophylactic doses completed uneventful pregnancies and gave birth to healthy babies (three for the first time) without complication. Bone density scans performed in all patients shortly after the delivery showed normal mineral mass. We conclude that LMW heparin does not cross the placental barrier, and in addition offers satisfactory antithrombotic protection for both maternal and placental circulation. In addition, this study provides preliminary data from 11 patients suggesting LMWH may not give rise to maternal osteoporosis, a finding that now needs further investigation.